A Federation Divided: Political Polarization and the Challenge to National Integration in Post-Election Pakistan 2024 - Dr. Waqar Un Nisa; Prof. Dr. Sultan Mahmood; Dr. Sumaira Bibi (Dialogue Social Science Review (DSSR), 2025)
The 2024 general elections in Pakistan, rather than providing a clear mandate for governance, have resulted in a deeply fragmented and polarized political landscape that poses a significant threat to the country's national integration. This paper examines the outcome of the elections, which saw the three mainstream political parties the Pakistan Muslim League-Nawaz (PML-N), the Pakistan People’s Party (PPP), and the Pakistan Tehreek-e-Insaf (PTI) assume power in the country's three largest provinces, Punjab, Sindh, and Khyber Pakhtunkhwa, respectively. This paper argues that this configuration, born from a controversial electoral process and set against a backdrop of profound institutional mistrust, is detrimental to Pakistan's democratic stability and national cohesion. It institutionalizes political rivalry at the provincial level, paralyzes federal governance on critical national issues, and exacerbates the already severe trust deficit between the state and its citizens. Drawing on the historical precedent of the 2006 Charter of Democracy, this paper concludes by proposing a series of actionable policy recommendations for political leadership. It calls for the urgent negotiation of a new, inclusive "National Compact" to establish functional rules of engagement, ensure the disengagement of the military from politics, and build consensus on institutional reforms, thereby creating a pathway toward national reconciliation and democratic survival.